Energy and nutrient consumption in Mexican women 12-49 years of age: analysis of the National Nutrition Survey 1999 - Barquera Simón; Rivera Juan A; Espinosa-Montero Juan; Safdie Margarita; Campirano Fabricio; Monterrubio Eric A (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To describe the reported energy and nutrient intake and adequacies in Mexican women. MATERIAL AND METHODS: A 24-hour dietary recall was used to obtain nutrient intake in a representative sub-sample of 2 630 women from 12 to 49 years of age from the National Nutrition Survey 1999. Nutrient adequacies were estimated using the Dietary Reference Intakes and stratified according to region, area (urban or rural), socioeconomic status and obesity status (non-obese: BMI <30 kg/m², obese: >30 kg/m²). Differences were analyzed using linear regression for complex surveys of log-transformed intake and adequacy, adjusting for multiple comparisons with the Bonferroni test. RESULTS: The median national energy intake was 1 471 kcal. The Risk of Inadequacy (RI) (prevalence of adequacy <50%) was: vitamin A:38.3%, vitamin C: 45.5%, and folate: 34.3%. Carbohydrates, folate, iron and calcium intake was significantly higher in rural than in urban areas. The RI was higher in women of the lowest socioeconomic status tertile for all nutrients with the exception of carbohydrates and calcium. Macro-nutrient adequacies were significantly higher in non-obese women. CONCLUSIONS: Differences within the country among regions, rural and urban areas, and socioeconomic status tertile reflect an increasing availability of inexpensive calorie-dense foods in marginal groups. However, total energy, cholesterol, saturated and total fat were consumed in greater quantities by women from the higher socioeconomic status tertile and from urban areas. These patterns could be a contributing factor to the rise of obesity and other non-communicable nutrition-related chronic diseases in Mexico.